IDENTIFIKASI PARIWISATA MEDAN MAIMUN DALAM LINGKUP ARSITEKTUR - Audrey Meyrizsa; Zorapatan Ajara (Jurnal Teknik dan Teknologi Indonesia, 2024)
Tourism and architecture are two things that cannot be separated in its development. Architecture plays an important role in organizing and maintaining a tourism area so that it can still provide a beautiful visual image. (Mill and Morrison, 1985). Architectural works, especially those that i k onik are used as attractions in the world of tourism and a da two roles of architecture, namely Menjadikan architectural works as objects of attraction and disain architecture to accommodate tourism activities. Taking into account the components of the tourism industry 5 A (attraction, accessibility, amenity, accommodation, awarness), then architectural works contribute to 3 components, namely Attraction: presenting artificial tourist destinations in the form of iconic areas buildings, Amenity: restaurant buildings, cafes, tourism information centers, museums and accommodation: hotel buildings, resorts, home stay. This study was conducted to find out more about maintaining a tourism area so that it can still provide a beautiful visual image. The theories used in this study are Empowerment theory, Social Capital Theory, Commodification Theory. This research uses a qualitative approach, using primary data as well as secondary data through observation, interviews and documentation. The data analysis technique used in this study is qualitativ.